The fifth gospel [compact disc, unabridged] : a novel - Caldwell, Ian, 1976- (Simon & Schuster Audio, 2015)
In 2004, as Pope John Paul II's reign enters its twilight, a mysterious exhibit is under construction at the Vatican Museums. A week before it is scheduled to open, its curator is murdered. The same night, a violent break-in rocks the home of the curator's research partner, Father Alex, a priest who lives inside the Vatican with his young son. When the papal police fail to identify a suspect in either crime, Father Alex, desperate to keep his family safe, undertakes his own investigation.